2022
DOI: 10.7759/cureus.32214
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Healthcare Practitioners Toward Therapeutic Drug Monitoring Practices in the Najran Region, Kingdom of Saudi Arabia

Abstract: Background: Therapeutic drug monitoring (TDM) is one of the useful clinical tools that aim to improve and ensure the best therapeutic effects while avoiding drug-related toxicity. We aimed to evaluate the knowledge and attitude toward TDM practices among healthcare practitioners in the Najran region, Saudi Arabia.Methodology: A cross-sectional study was conducted between May 2021 and October 2021 for assessing the awareness and attitude of licensed doctors and pharmacists working in Saudi Arabia regarding TDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, the findings also revealed that TDM was implemented in less than half of the surveyed hospitals and mostly at large sites (> 500 beds). Several reasons for not conducting TDM were identified, including the lack of an in-house TDM laboratory, which has also been determined to be a primary obstacle in other studies (Al Mutarid et al, 2022;Antunes et al, 2021). In TDM, immunoassay techniques and liquid chromatography (LC) are widely employed as analytical methods (Salamone et al, 2023).…”
Section: Barriers To Tdm Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings also revealed that TDM was implemented in less than half of the surveyed hospitals and mostly at large sites (> 500 beds). Several reasons for not conducting TDM were identified, including the lack of an in-house TDM laboratory, which has also been determined to be a primary obstacle in other studies (Al Mutarid et al, 2022;Antunes et al, 2021). In TDM, immunoassay techniques and liquid chromatography (LC) are widely employed as analytical methods (Salamone et al, 2023).…”
Section: Barriers To Tdm Implementationmentioning
confidence: 99%
“…While some regions in South America and Europe (Antunes et al, 2021;Zhang et al, 2021;Green et al, 2022) have incorporated pharmacogenetics into TDM service at the research level and Australia (Firman et al, 2022) and the USA (Pedersen et al, 2016) have initiated programmes where pharmacists can order and interpret laboratory tests for TDM and adjust the drug dose without consulting with doctors, another country has reported a lack of trained pharmacists or clinical pharmacologists to interpret and provide clinical recommendations in TDM (Yin et al, 2023). Previous research exploring TDM practices in various countries has identified several challenges to establishing and advancing TDM services (Antunes et al, 2021;Albassam et al, 2022;Al Mutarid et al, 2022). These obstacles include a lack of suitable TDM laboratories within hospitals, insufficient space for conducting TDM tests or storing biological specimens, inadequate funding for the measurement of drug levels, staff shortages, inaccessibility to the relevant training and limited awareness regarding the importance of TDM.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental goal of TDM is to personalize the dosage to achieve the highest level of therapeutic efficacy and minimize drug-related adverse effects. Partially available in Saudi Arabia and Kuwait, TDM services can provide an excellent pharmacological response with fewer adverse toxic drug effects [ 57 ]. Many hospitals affiliated with the Ministry of Health in Saudi Arabia have recently started offering TDM services as a regular aspect of patient management and drug monitoring [ 57 ].…”
Section: Reviewmentioning
confidence: 99%
“…Partially available in Saudi Arabia and Kuwait, TDM services can provide an excellent pharmacological response with fewer adverse toxic drug effects [ 57 ]. Many hospitals affiliated with the Ministry of Health in Saudi Arabia have recently started offering TDM services as a regular aspect of patient management and drug monitoring [ 57 ]. More such collaborations are warranted to enhance TDM activities in these countries and to make TDM available across the region (Figure 2 ).…”
Section: Reviewmentioning
confidence: 99%
“…In the real-world clinical practice, however, the implementation of regular TDM is not always possible. For example, research conducted by Al Mutarid and colleagues found that although the practice of TDM was well known among doctors in Saudi Arabia, its actual use was poorly applicated, especially in smaller hospitals, mainly because of lack of resources [12]. Another study, conducted in Turkey by Eryılmaz and colleagues, found a positive approach in the frequency of TDM use among Turkish clinicians for mood stabilizers, with 98.4% of clinicians declaring regular use of TDM, especially for lithium and valproate, but with significantly lower rates of monitoring for other classes of psychotropic medications [13].…”
Section: Introductionmentioning
confidence: 99%